Kinetics of Cation Desorption from Heterogeneous Solid Surface at Very Low Coverage - Edward W. Thornton; Guy Renn (Adsorption Science & Technology)
Cations desorb from solid surfaces into elecrolyte solutions slowly at very low coverages. The kinetics of this slow desorption were studied using radioactive tracers in a flow cell experiment. On a number of real adsorbents the kinetics are explained by rate limiting desorption from random, weakly heterogeneous surface sites. Slow desorption is not liquid phase diffusion-controlled. The distribution of adsorption site energies which accounts for the desorption kinetics also gives rise to the Freundlich adsorption isotherm. Desorption rates into simple electrolytes depend upon pH and ionic strength; a primitive model of the interfacial region accounts for yttrium ion desorption rates from a polyurethane into NaNO 3 + HNO 3 /NaOH solutions.